Correlation between dry matter intake and weight gain in bali cattle (Journal of Tropical Pharmacy and Chemistry, 2025)
Beef cattle productivity is strongly influenced by the quality and quantity of feed provided. Dry matter intake (DMI) is a key indicator of nutritional adequacy. Previous studies have been largely descriptive and have not emphasized the quantitative relationship between DMI and growth performance of Bali cattle under intensive smallholder farming systems.This study analyzed the correlation between dry matter intake and body weight gain in male Bali cattle raised intensive management. The research was conducted in Kutai Kartanegara Regency, East Kalimantan Province, involving 45 respondents, with a total of 180 male Bali cattle. Data were collected through field surveys, body weight measurements, and laboratory analyses of the feed dry matter content. Statistical analyses were performed using Pearson’s correlation and simple linear regression.The results indicated that the average daily body weight gain of the Bali cattle reached 0.48 kg/head/day. Dry matter intake was positively and significantly correlated with body weight gain (r= 0.777; p < 0.01) using the regression equation Y= 8.159 + 0.483X. These findings confirm that increasing the DMI directly enhances the growth performance of Bali cattle.The study concluded that feed management emphasizing dry matter intake optimization is essential to support the productivity of local beef cattle.